Pemberdayaan Potensi Diri dalam Kewirausahaan pada Anggota Posyandu Remaja di Kecamatan Bubutan Surabaya - Tiara Diah Sosialita; Reza Lidia Sari; Valina Khiarin Nisa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Based on the need analysis conducted, the problems are Bubutan subdistrict of Surabaya City has a large number of young people, but it is not balanced with productivity. In this stage, adolescents should be directed to carry out positive activities by their interests. Results of the initial assessment found that young people in Bubutan are interested in the field of entrepreneurship. Still, unfortunately, most of them did not have basic entrepreneurial knowledge and skill. The solution that is expected to be effective for those problems is an entrepreneurship education program to empower self-potential in the entrepreneurial field. In fact, the implementation of this program can be a solution to the need of young people in Bubutan, which was lack entrepreneurial education. This program was given to Posyandu Remaja with consideration that they can become initiators for other adolescents to develop productivity, quality, and self-character in the industrial era 4.0, which demands global competition.